ANALISIS PENGARUH MOTIVASI KERJA DAN KOMPETENSI TERHADAP KINERJA KARYAWAN BAGIAN PRODUKSI PADA PT. GROWTH ASIA MEDAN - Sahat Simbolon (Jurnal Manajemen Akuntansi Dan Administrasi Bisnis, 2018)
The purpose of this research is to analyze the influence of work motivation, and competence to employee performance of production at PT Growth Asia Medan. The research was conducted on the employee of PT Growth Asia Medan with population of 320 people. Samples were taken as many as 80 people. The data were collected by using questionnaire method and documentation technique. Data were analyzed by using descriptive method and multiple linear regression analysis. Partial test result (t test) proves that motivation have positive but not significant effect to employee performance, while competence have positive and significant influence to employee performance of PT Growth Asia Medan. Simultaneous test (F test) shows that the motivation of work and competence simultaneously have a significant effect on employee performance. The coefficient of determination (R2) of 0.703 means that 70.3% of employee performance of PT Growth Asia Medan is influenced by work motivation and work competence of employees, while the remaining 29.7% is influenced by other variables not examined in this research, for example leadership variable, work commitment, work culture, work environment, compensation, and so forth. Leaders need to pay attention to job performance, giving bonus, direction, and improvement of work motivation to employees.